2008
DOI: 10.1371/journal.pone.0004016
|View full text |Cite
|
Sign up to set email alerts
|

Wind, Waves, and Wing Loading: Morphological Specialization May Limit Range Expansion of Endangered Albatrosses

Abstract: Among the varied adaptations for avian flight, the morphological traits allowing large-bodied albatrosses to capitalize on wind and wave energy for efficient long-distance flight are unparalleled. Consequently, the biogeographic distribution of most albatrosses is limited to the windiest oceanic regions on earth; however, exceptions exist. Species breeding in the North and Central Pacific Ocean (Phoebastria spp.) inhabit regions of lower wind speed and wave height than southern hemisphere genera, and have larg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
57
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(60 citation statements)
references
References 25 publications
1
57
2
Order By: Relevance
“…This may be reflected in the gradual shift of bathymetrically linked habitat preference that we observed. Previous tracking suggested that juveniles are traveling twice the distances per day that adult birds travel (Suryan et al 2008). We found seasonal differences in daily travel distances but we did not observe an ontogenetic shift in travel distance for our birds.…”
Section: Discussioncontrasting
confidence: 65%
See 1 more Smart Citation
“…This may be reflected in the gradual shift of bathymetrically linked habitat preference that we observed. Previous tracking suggested that juveniles are traveling twice the distances per day that adult birds travel (Suryan et al 2008). We found seasonal differences in daily travel distances but we did not observe an ontogenetic shift in travel distance for our birds.…”
Section: Discussioncontrasting
confidence: 65%
“…It is uncertain, however, why immature birds occupy regions not typically used by adults. Such differences in distribution could be driven by innate differences in the foraging capacity, aerodynamic performance between immatures and adults (Shaffer et al 2001a, Suryan et al 2008, or by timing and energetic constraints (e.g. molt, recovery from reproduction) faced by annually breeding birds that prevent them from visiting more distant seasonally productive regions (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…This leads to the interesting irony that while flying animals are celebrated for their ability to escape the apparent bonds of the ground, many of them exploit, and in some cases depend on [40], heterogeneity in the airscape that derives from the air's interaction with the substrate, rendering them less 'free' than we might imagine them to be. In support of this, there is increasing evidence that the distribution of a range of highly aerial species is fundamentally linked to the properties of the aerial environment [41,42]. Ultimately, the extent to which animals vary their flight paths in relation to airflows will depend on the interplay between internal and external factors (cf.…”
Section: Flow Selection (A) Detecting Wind Directionmentioning
confidence: 99%
“…Recent research has highlighted the effects of wind on the energetic and temporal costs incurred by seabirds during flight (Weimerskirch et al 2000, Suryan et al 2008. Flight performance is partly dependent on wing loading, leading to suggestions that birds with higher wing loadings are better adapted to windier areas (Shaffer et al 2001, Suryan et al 2008.…”
Section: Habitat Availability and Accessibilitymentioning
confidence: 99%
“…Flight performance is partly dependent on wing loading, leading to suggestions that birds with higher wing loadings are better adapted to windier areas (Shaffer et al 2001, Suryan et al 2008. Migrating and breeding Procellariiformes route their journeys and make behavioral decisions so as to exploit favorable winds at fine to mega-scales (Murray et al 2003, Felicisimo et al 2008).…”
Section: Habitat Availability and Accessibilitymentioning
confidence: 99%